Principal Sorting and the Distribution of Principal Quality - Jason A. Grissom; Brendan Bartanen; Hajime Mitani (SAGE Publishing, 2019)
Numerous studies document the inequitable distribution of teacher quality across schools. We focus instead on the distribution of principal quality, examining how multiple proxies for quality, including experience, teachers' survey assessments of leaders, and rubric-based practice ratings assigned by principals' supervisors, vary by measures of school advantage, using administrative data from Tennessee. By virtually every quality measure, we find that schools serving larger fractions of low-income students, students of color, and low-achieving students are led by less qualified, less effective principals. These patterns persist across urban, suburban, and rural settings. Both differential hiring/placement and differential turnover patterns by principal quality across school characteristics contribute to these patterns. Simulation evidence suggests that hiring and turnover vary in relative importance to principal sorting patterns according to the measure of quality examined and that differential principal improvement across contexts may matter as well. Complementary analyses of national survey data corroborate our main results.